2020
DOI: 10.1002/ese3.728
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the permeability of fractured sandstone under complex stress paths

Abstract: Oil and gas are main storage resources in the pores and fractures of rocks. Under a complex stress environment, the permeability evolution of the reservoir rock fracture directly affects the flow of oil and gas, which is important in oil and gas exploration and development. The permeability test of a single sample in complex stress paths was performed on intact sandstone, single‐fractured sandstone, and double‐fractured sandstone using high‐precision hydro‐mechanics‐coupled triaxial experimental equipment to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…As the formation pressure decreases, their stress sensitivity is stronger than conventional reservoirs (Figure 2). Many scholars have studied stress sensitivity effects in tight reservoirs through physical simulation experiments and numerical simulation techniques and have built corresponding permeability models [27][28][29]. Based on the relationship model between porosity and permeability, Mckee et al proposed an exponential model between permeability and effective stress using rock mechanics theory [30].…”
Section: Model Construction and Solutionmentioning
confidence: 99%
“…As the formation pressure decreases, their stress sensitivity is stronger than conventional reservoirs (Figure 2). Many scholars have studied stress sensitivity effects in tight reservoirs through physical simulation experiments and numerical simulation techniques and have built corresponding permeability models [27][28][29]. Based on the relationship model between porosity and permeability, Mckee et al proposed an exponential model between permeability and effective stress using rock mechanics theory [30].…”
Section: Model Construction and Solutionmentioning
confidence: 99%
“…Compared to intact sandstone, single‐fracture sandstone, and double‐fracture sandstone have been found to have significantly greater permeability. This was determined in a study where the permeability of these three types of sandstone was compared 7 . Zhao et al 8 conducted research on the seepage behavior of fracture networks after hydraulic fracturing of shale and concluded that the seepage channels formed during the process can significantly enhance the permeability of shale.…”
Section: Introductionmentioning
confidence: 99%
“…This was determined in a study where the permeability of these three types of sandstone was compared. 7 Zhao et al 8 conducted research on the seepage behavior of fracture networks after hydraulic fracturing of shale and concluded that the seepage channels formed during the process can significantly enhance the permeability of shale. In addition, hydraulic fracturing is also used in the commercial development of oil and gas wells to increase production.…”
mentioning
confidence: 99%
“…Studies have shown that the permeability of mudstone at room temperature is affected by triaxial stress and pore pressure, that is, it decreases with the i ncrease of effective stress [4][5][6][7][8][9]. Temperature also has a significant effect on th e permeability of rocks.…”
Section: Introductionmentioning
confidence: 99%